Nations and nationalism since 1780 : programme, myth, reality - Hobsbawm, E. J. (Eric J.), 1917-2012 (Cambridge University Press, 1992)
Eric Hobsbawm's brilliant enquiry into the question of nationalism won further acclaim for his 'colossal stature ... his incontrovertible excellence as an historian, and his authoritative and highly readable prose'. Recent events in Eastern Europe and the former Soviet republics have since reinforced the central importance of nationalism in the history of political evolution and upheaval. This second edition has been updated in the light of those events, with a final chapter addressing the impact of the dramatic changes that have taken place. It also includes additional maps to illustrate nationalities, languages and political divisions across Europe in the nineteenth and twentieth centuries.